2010
DOI: 10.1111/j.1365-2141.2009.08020.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C action in inflammation

Abstract: Summary Activated protein C (APC) is a natural anticoagulant that plays an important role in coagulation homeostasis by inactivating the procoagulation factor Va and VIIIa. In addition to its anticoagulation functions, APC also has cytoprotective effects such as anti‐inflammatory, anti‐apoptotic, and endothelial barrier protection. Recently, a recombinant form of human APC (rhAPC or drotrecogin alfa activated; known commercially as ‘Xigris’) was approved by the US Federal Drug Administration for treatment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 139 publications
(159 reference statements)
1
57
0
Order By: Relevance
“…These clinical finding are supported by studies in sheep, demonstrating that treatment with rhAPC in endotoxin or peritoneal-induced sepsis can reduce lung edema and injury (Waerhaug et al, 2008;Wang et al, 2007). Although APC is known for its anti-coagulative effects, these alone can not account for the improved clinical outcome in septic patients, since targeting of either activated factor X, anti-thrombin or tissue factor inhibitors has failed to produce a comparative protection (Sarangi et al, 2010). As such, APC has also been described to induce several cytoprotective effects which likely contribute to its success in the treatment of sepsis.…”
Section: Activated Protein C (Apc)supporting
confidence: 61%
See 1 more Smart Citation
“…These clinical finding are supported by studies in sheep, demonstrating that treatment with rhAPC in endotoxin or peritoneal-induced sepsis can reduce lung edema and injury (Waerhaug et al, 2008;Wang et al, 2007). Although APC is known for its anti-coagulative effects, these alone can not account for the improved clinical outcome in septic patients, since targeting of either activated factor X, anti-thrombin or tissue factor inhibitors has failed to produce a comparative protection (Sarangi et al, 2010). As such, APC has also been described to induce several cytoprotective effects which likely contribute to its success in the treatment of sepsis.…”
Section: Activated Protein C (Apc)supporting
confidence: 61%
“…As such, APC has also been described to induce several cytoprotective effects which likely contribute to its success in the treatment of sepsis. These mechanisms include: 1) decreasing apoptosis (Mosnier et al, 2007), 2) the ability to bind to nuclear ribonucleoproteins, thereby facilitating the clearance of nuclear material from injured and necrotic tissue (Jean-Baptiste, 2007), 3) mediating the protection of the endothelial barrier, which prevents the destructive massive infiltration of neutrophils , 4) a number anti-inflammatory effects including the decrease of tissue factor and thrombin, which in turn can induce inflammation, and the blockade of NFκB, which subsequently decreases the direct up-regulation of cytokines (Sarangi et al, 2010). Future studies, including the current multi-centered, phase III clinical trial PROWESS SHOCK (clinicaltrials.gov NCT00604214), are likely to further investigate and clarify the various mechanisms involved in APC-induced ALI protection during sepsis.…”
Section: Activated Protein C (Apc)mentioning
confidence: 99%
“…It acts as a natural anticoagulant by inactivating the coagulation factors Va and VIIIa (4). In addition, activated protein C has antiinflammatory effects and can support the vascular endothelial barrier (5), which, altogether, has shown to be protective in severe human sepsis (6). In fact, a recombinant form of human activated protein C (Drotrecogin alfa activated; commercially known as Xigris; Lilly Deutschland, Bad Homburg, Germany) was approved in 2001 by the U.S. Food and Drug Administration for the treatment of severe sepsis and high risk of death (7).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…In fact, a recombinant form of human activated protein C (Drotrecogin alfa activated; commercially known as Xigris; Lilly Deutschland, Bad Homburg, Germany) was approved in 2001 by the U.S. Food and Drug Administration for the treatment of severe sepsis and high risk of death (7). Although the precise way of action has not yet been elucidated (5,8), the immunosuppressive and cytoprotective effects of activated protein C now emerge as a potential treatment for a number of other diseases that are associated with excessive immune responses such as acute respiratory distress syndrome, multiple sclerosis, rheumatoid arthritis, brain injury, stroke, and chronic wounds (9)(10)(11)(12). A recent study reported that activated protein C was also effective in protecting against diabetic nephropathy by inhibiting endothelial and podocyte apoptosis, where it modulates the mitochondrial apoptosis pathway via the protease-activated receptor-1 (PAR-1) and the endothelial protein C receptor (EPCR) (13).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Its anticoagulant competence enhances, due to the modulation of the thrombin activity through two mechanisms, inhibition of prothrombin converting into thrombin and promotion of thrombin inversion from a procoagulant enzyme into an anticoagulant one. Inhibition of thrombin formation can also reduce thrombin's proinflammatory activities (Sarangi et al, 2010). In a complementary mode with respect to anticoagulation, the surplus clots are dissolved by proteases of the fibrinolytic system.…”
Section: Termination Phase Of the Coagulation Processmentioning
confidence: 99%